Toleration, Power and Reason: Continuing a Dialogue with a Political Realist Friend - Rainer Forst (Biblioteca della libertà, 2019)
In this essay, I continue a dialogue with Glen Newey about the normative and political possibility of a conception of toleration that aims at a higher-order justification of its grounds and limits. I argue for such a conception, Glen remained skeptical about it.
Keywords: 330